Automated synthesis of [68Ga]Ga-FAPI-46 without pre-purification of the generator eluate on three common synthesis modules and two generator types - Ammar Alfteimi; Ulf Lützen; Alexander Helm; Michael Jüptner; Marlies Marx; Yi Zhao; Maaz Zuhayra (EJNMMI Radiopharmacy and Chemistry, 2022)
Abstract Background The recent development of quinoline-based radiotracers, which act as fibroblast activation protein inhibitors (FAPIs), has shown promising preclinical and clinical advantages. [68Ga]Ga-FAPI-46 is a new radiotracer for in vivo detection of the fibroblast activation protein by positron emission tomography (PET). Recently, the automated synthesis of [68Ga]Ga-FAPI-46 was reported based on pre-concentration and purification of the generator eluate by using a cation exchange-cartridge. Our aim was to simplify the synthesis and shorten the automated synthesis of [68Ga]Ga-FAPI-46 to make it accessible and thus even more attractive to a broader clinical and scientific community. Results We developed and evaluated the GMP compliant automatic synthesis of [68Ga]Ga-FAPI-46 using two different 68Ge/68Ga generators (an Eckert & Ziegler, GalliaPharm generator, 1.85 GBq/50 mCi and an iThemba generator, 1.85 GBq/50 mCi) Somerset West, South Africa) and three different commercial and customized systems: the EasyOne module from Trasis; the GaSy module from Synthra with a customized synthesis template and a customized single use cassette. Additionally, the automatic synthesis of [68Ga]Ga-FAPI-46 was established on a GallElut synthesis module from Scintomics with fixed tubing. Conclusions Independent of the synthesis modules or the generators employed we were able to complete the synthesis of [68Ga]Ga-FAPI-46 in 12 min including the process of purification and formulation. In all cases, the final products showed more than 99.5% chemical purity and the radiochemical yield reached around 92.5% (decay corrected). All quality control parameters (e.g. sterility, stability and radiochemical purity) were conform to the European Pharmacopoeia.